The research aims to study the novel Frankenstein in Baghdad, study the characters present and analyze them in the novel, and also study isolation in the homeland and the post-war social reality and analyze the reasons that make isolation a part of the i (Journal of Imam Al-Kadhim College, 2023)
The research aims to study the novel Frankenstein in Baghdad, study the characters present and analyze them in the novel, and also study isolation in the homeland and the post-war social reality and analyze the reasons that make isolation a part of the individual’s personality due to circumstances or the nature of life. Post-colonial literature in Iraq contains much of the tragic reality of wars. The research focused on the main characters and reflected on the theme of isolation.The research is interested in studying post-colonial literature in Iraq or war literature by studying society and political and social problems such as corruption and moral decay and their reflection on the characters. Literature is a reflection of reality and a direct picture of all aspects of society. The important events that lead to destruction, terror, and terrorism and how they shape the image of the individual in this society. Discussing these conditions and variables and studying the extent of their impact on the individual’s behavior.The research concluded that war and political corruption destroy society. The disastrous consequences of wars were discussed, how corruption spread, the destruction of love between Iraqi families, hunger and poverty. Friends become enemies and begin to doubt each other. The lack of security and the disintegration of all administrative systems force citizens to leave their homeland and migrate elsewhere. Those who have no alternative continue to survive amidst danger. Some have no choice, like Hadi, or others have a reason to stay home, like Elisheva. However, one thing is certain. Those unfortunate beings who stay, for whatever reason, feel isolated and abandoned by their homeland. Nothing could be more tragic than this. They are physically separated from their family members